Portion size of food affects energy intake in normal-weight and overweight men and women - Rolls, Barbara J; Morris, Erin L; Roe, Liane S (The American journal of clinical nutrition, 2002)
Background: Large portions of food may contribute to excess energy intake and greater obesity. However, data on the effects of portion size on food intake in adults are limited. Objectives: We examined the effect of portion size on intake during a single meal. We also investigated whether the response to portion size depended on which person, the subject or the experimenter, determined the amount of food on the plate. Design: Fifty-one men and women were served lunch 1 d/wk for 4 wk. Lunch included an entrée of macaroni and cheese consumed ad libitum. At each meal, subjects were presented with 1 of 4 portions of the entrée: 500, 625, 750, or 1000 g. One group of subjects received the portion on a plate, and a second group received it in a serving dish and took the amount they desired on their plates. Results: Portion size significantly influenced energy intake at lunch (P < 0.0001). Subjects consumed 30% more energy (676 kJ) when offered the largest portion than when offered the smallest portion. The response to the variations in portion size was not influenced by who determined the amount of food on the plate or by subject characteristics such as sex, body mass index, or scores for dietary restraint or disinhibition. Conclusions: Larger portions led to greater energy intake regardless of serving method and subject characteristics. Portion size is a modifiable determinant of energy intake that should be addressed in connection with the prevention and treatment of obesity.